Preparation of poly (N-isopropylacrylamide/itaconic acid) copolymeric hydrogels and their drug release behavior - KAYAMAN APOHAN, NİLHAN (ELSEVIER, 2004)
N-isopropylacrylamide/itaconic acid copolymeric hydrogels were prepared by irradiation of the ternary mixtures of N-isopropylacrylamide/itaconic acid/water by gamma-rays at ambient temperature. The effect of comonomer concentration, irradiation dose and pH on the swelling equilibria were studied. Lidocaine was used as a model drug for the investigation of drug release behaviour of hydrogels. Lidocaine adsorption capacity of the hydrogels were found to increase from 3.6 to 862.1 (mg lidocame/g dry gel) with increasing amount of itaconic acid in the gel structure. Adsorption and release processes were followed at 4 and 37 degreesC, respectively. The release studies showed that the basic parameters affecting the drug release behaviour of the hydrogels were pH and temperature of the solution and cross-link density of the gels. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: hydrogel; N-isopropylacrylamide; itaconic acid; lidocaine; drug release